Five-year results of a prospective clinical trial investigating accelerated partial breast irradiation using 3D conformal radiotherapy after lumpectomy for early stage breast cancer. (August 2016) - Horst, Kathleen C.; Fasola, Carolina; Ikeda, Debra; Daniel, Bruce; Ognibene, Grant; Goffinet, Don R.; Dirbas, Frederick M.
Abstract: Background: Accelerated partial breast irradiation (APBI) is emerging as an alternative to whole-breast irradiation. This study presents the results of a prospective trial evaluating 3-dimensional conformal radiotherapy (3D-CRT) to deliver APBI for early-stage breast cancer. Methods: Patients with unifocal stage 0–II breast cancer measuring ≤2.5 cm without lymph node involvement were eligible. After lumpectomy, 3D-CRT APBI was delivered to the lumpectomy cavity + margin (34–38.5 Gy in 10 fractions over 5 days). Results: 141 patients with 143 breast cancers (2 bilateral) were treated with 3D-CRT APBI. Median age was 60. Median tumor size was 1.1 cm. At a median follow up of 60 months (range, 5–113), the 5-year and 8-year cumulative incidence rate of a true recurrence is 0.9%. The 5-year and 8-year cumulative incidence rates of an elsewhere failure are 2.4% and 4.4%, respectively. The 5-year and 8-year overall survival is 100% and 94%, respectively. Among the 62 patients with follow up >5 years, 95% had excellent/good cosmetic results. Conclusions: Our experience with 3D-CRT APBI demonstrates excellent cosmesis and local control. Longer follow up will be necessary to evaluate long-term efficacy and toxicity of 3D-CRT APBI. ClinicalTrials.gov Identifier: NCT00185744 . Highlights: Our results of 3D-CRT APBI demonstrate minimal toxicity and excellent cosmesis. Few local recurrences occurred; all were in patients who refused systemic therapy. 3D-CRT APBI may be appropriate in select patients.